The embedding theorems for anisotropic Nikol’skii-Besov spaces with generalized mixed smoothness - Bekmaganbetov, K.A.; Kervenev, K.Ye.; Toleugazy, Ye. (Bulletin of the Karaganda University. Mathematics Series, 2021)
The theory of embedding of spaces of differentiable functions studies the important relations of differential (smoothness) properties of functions in various metrics and has a wide application in the theory of boundary value problems of mathematical physics, approximation theory, and other fields of mathematics. In this article, we prove the embedding theorems for anisotropic spaces Nikol’skii-Besov with a generalized mixed smoothness and mixed metric, and anisotropic Lorentz spaces. The proofs of the obtained results are based on the inequality of different metrics for trigonometric polynomials in Lebesgue spaces with mixed metrics and interpolation properties of the corresponding spaces.